PERIODIC DISEASE IN CHILDREN. CLINICAL CASE - U.N. Klochkova; I.M. Vazhnova (Union of pediatricians of Russia, 2010)
Patients with periodical disease (PD) are found frequently enough in specific ethnic groups. The relevance of this topic, however, is also driven by an early debut of pathology and in most cases by a serious prognosis for the patient's life in the event of late disease detection and treatment. It is not uncommon that diagnostic errors may result in unjustified operational intervention. Key words: periodical disease, children. (Pediatric Pharmacology. - 2010; 7(1):85-87)